Morphological Characteristics of Four Atriplex Species (Atriplex ssp.) in Wadi Al-Azeeb Station - Marouf, Ahlam; AL-Ouda, Ayman; Babojian, Gorgeet (Latakia University Journal -Biological Sciences Series, 2013)
Atriplex is one of good adaptive plants to the Characteristics of drought fragile environments, and it has high ability to tolerate many ecological stresses such as drought and high temperature and salinity. The plant is characterized by its huge economic values because it has many uses, it’s one of the high digestibility grazing plants and it is grazing by camels, goats and sheep all the year, some of them have medicinally uses in repairing the increasing of blood sugar, the freshness parts of some species use in preparing salads, even they have cook using, and leaves usually have a salty taste even the plant grow in none salinity soils. The morphological variety of four species of Atriplex were studying, two of them are introduced (A. canescens, A. polycarpa) and two have natural spreading in Syria (A. leucoclada, A. halimus). The results indicated that biological type, life duration, plants color, fruit bracts shape and fused of fruit bracts, plant smell, seed color, leaves shape and phyllotaxy are considered the most morphological characters which show important morphological differences among the studying species. These can be considered among classification standards to help distinguish the studying species of Atriplex genus under their natural spreading land, which consider the natural habitat for this important plant. Based on studied morphological characters, an identification key for the studying species is provided.